Mindfulness as a protective factor against depressive symptoms in people with fibromyalgia. (3rd March 2020) - Brooks, Jessica M.; Muller, Veronica; Sánchez, Jennifer; Johnson, Eboneé T.; Chiu, Chung-Yi; Cotton, Brandi P.; Lohman, Matthew C.; Catalano, Denise; Bartels, Stephen; Chan, Fong
Abstract: Background : Depressive symptoms complicate pain management for people with FM, with adverse consequences such as a greater need for pain medications and limited pain coping strategies. Determining risks and protective factors associated with depressive symptoms in persons with FM could inform the development and implementation of mental health interventions. Aims : To formulate and test a behavioral activation model of depression with mindfulness as a protective factor for people with FM. Methods : We conducted an online cross-sectional survey with 117 adults with FM from community and clinic networks. Path analysis was used to assess the relationships of pain intensity, perceived stress, activity interference, pain catastrophizing and mindfulness with depressive symptoms. Results : Mindfulness has a negative direct association with depressive symptoms and a negative indirect association with depressive symptoms through perceived stress, activity interference and pain catastrophizing. Perceived stress, activity interference and pain catastrophizing had direct associations with depressive symptoms. Finally, perceived stress, activity interference and pain catastrophizing had indirect associations with depressive symptoms through pain intensity. Conclusions : Mindfulness seems to play an important role as a protective factor against the negative effects of stress and depression among people with FM and should be included in mental health interventions for chronic pain.